Gut Permeability in Autism Spectrum Disorders. Issue 3 (12th December 2013) - Dalton, Neil; Chandler, Susie; Turner, Charles; Charman, Tony; Pickles, Andrew; Loucas, Tom; Simonoff, Emily; Sullivan, Peter; Baird, Gillian
<x xml:space="preserve">Abstract</x> Objective To test whether gut permeability is increased in autism spectrum disorders (ASD) by evaluating gut permeability in a population‐derived cohort of children with ASD compared with age‐ and intelligence quotient‐matched controls without ASD but with special educational needs (SEN). Patients and Methods One hundred thirty‐three children aged 10–14 years, 103 with ASD and 30 with SEN, were given an oral test dose of mannitol and lactulose and urine collected for 6 hr. Gut permeability was assessed by measuring the urine lactulose/mannitol (L/M) recovery ratio by electrospray mass spectrometry‐mass spectrometry. The ASD group was subcategorized for comparison into those without (n = 83) and with (n = 20) regression. Results There was no significant difference in L/M recovery ratio (mean (95% confidence interval)) between the groups with ASD: 0.015 (0.013–0.018), and SEN: 0.014 (0.009–0.019), nor in lactulose, mannitol, or creatinine recovery. No significant differences were observed in any parameter for the regressed versus non‐regressed ASD groups. Results were consistent with previously published normal ranges. Eleven children (9/103 = 8.7% ASD and 2/30 = 6.7% SEN) had L/M recovery ratio > 0.03 (the accepted normal range cut‐off), of whom two (one ASD and one SEN) had more definitely pathological L/M recovery ratios > 0.04. Conclusion There is no statistically significant group difference in small intestine permeability in a population cohort‐derived group of children with ASD compared with a control group with SEN. Of the two children (one ASD and one SEN) with an L/M recovery ratio of > 0.04, one had undiagnosed asymptomatic celiac disease (ASD) and the other (SEN) past extensive surgery for gastroschisis. Autism Res2014, 7: 305–313. © 2013 International Society for Autism Research, Wiley Periodicals, Inc.